Reframing Concept of Governance in Public Administration Researches: A Philosophical Discussion - Yani, Andi Ahmad (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2018)
The concept of governance is widely employed in various field of studies. Governance also commonly employed to characterize institutions both in public sector institutions and private domains, describe both formal and informal organizations, and define both international and local networks. In the field of public administration, the concept of governance has been explored in last three decades. The usage of the word of governance could be in diverse ways and has various meanings which seems that governance is tend to be applied as rhetorical reasons rather than theoretical argumentations. This review article provides two philosophical approaches to understand governance concept in public administration study. They are pragmatic philosophy and phenomenology philosophy. Both philosophical approaches provide dynamic and complex issues that be considering by public administration scholars in future research agendas.